1996
DOI: 10.5144/0256-4947.1996.609
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor in Falciparum Malaria

Abstract: To investigate the relationship of TNFα levels to Plasmodium falciparum (PF) infection, plasma TNFα concentrations were measured in Pakistani adults and children with mild, severe, cerebral and chronic falciparum malaria and healthy (control) subjects. The initial geometric mean plasma concentrations of TNFα in adult patients with severe malaria (187.6 pg/mL) were significantly higher than mild malaria patients (87.1 pg/mL, P < 0.001). TNFα levels were not correlated to parasite density, cerebral malaria, youn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…3,16 Other studies have also discussed the role of TNF-α in falciparum malaria. 18 In a recent report, the investigators' observations indicated that hemolysis is the prime cause of the anemia seen in acute falciparum malaria, but destruction of parasitized erythrocytes is not the only cause of the hemolytic process, and bone marrow suppression appears to have an insignificant role. 19 It should be borne in mind also that red cell morphology in malaria patients may be influenced by their nutritional status i.e., patients could be iron deficient, folic acid or vitamin B 12 deficient or they may have a concurrent thalassemia, which aggravates the severity of the anemia, as was the case in some of the patients in this study.…”
Section: Discussionmentioning
confidence: 99%
“…3,16 Other studies have also discussed the role of TNF-α in falciparum malaria. 18 In a recent report, the investigators' observations indicated that hemolysis is the prime cause of the anemia seen in acute falciparum malaria, but destruction of parasitized erythrocytes is not the only cause of the hemolytic process, and bone marrow suppression appears to have an insignificant role. 19 It should be borne in mind also that red cell morphology in malaria patients may be influenced by their nutritional status i.e., patients could be iron deficient, folic acid or vitamin B 12 deficient or they may have a concurrent thalassemia, which aggravates the severity of the anemia, as was the case in some of the patients in this study.…”
Section: Discussionmentioning
confidence: 99%
“…[36] Research studies also suggest that increased IL-6 levels have a strong association with increase in transferrin receptor density, and decreased transferrin synthesis which play a significant role in anemic severity. [3536] Our observation of a negative correlation between decreased Hb levels and increased IL-6 suggests that higher IL-6 production which may contribute to the pathogenesis of SMA. [25]…”
Section: Discussionmentioning
confidence: 96%
“…IL-6 also could play a role in inflammatory response and pathophysiology of SMA. [35] It is well known that IL-6 production is upregulated by TNF-α and acts together with other inflammatory mediators to reduce the parasitic burden. In this study, in comparison to HC, we observed increased IL-6 levels among infected patients and a reciprocal relationship was also observed between increasing parasitemia and IL-6 levels.…”
Section: Discussionmentioning
confidence: 99%